Tax reliefs for young families and for children - Tsvetanova, Marina (Law Journal of New Bulgarian University, 2023)
The article examines the tax reliefs related to families and parents in the Bulgarian national legal system as the only tax policy measures for rising the birth rate, stimulating people to get married and for a more equal income distribution within this group of taxpayers. As a comparison the article presents the German family income tax system with the tax brackets.